CompTIA Network+ Review Guide Exam N10-008. - Buhagiar, Jon (John Wiley & Sons, Incorporated, 2021)
Prep for success on the Network+ N10-008 exam and for your new career in network administration with this must-have resource In the newly updated Fifth Edition of the CompTIA Network+ Review Guide: Exam: N10-008, a leading expert in Network Operations, Jon Buhagiar, delivers a focused and concise handbook for anyone preparing for the new Network+ N10-008 exam or for a career in network administration. This guide is organized into five parts, with each part corresponding to one of the 5 objective domain areas of the Network+ exam: Fundamentals, Implementations, Operations, Security, and Troubleshooting. You'll handily learn crucial IT skills like designing and implementing functional networks, configuring and managing essential network devices, using switches and routers to segment network traffic, and securing existing networks. This book also allows you to: Quickly and comprehensively prepare for the Network+ N10-008 exam with intuitively organized info and efficient learning strategies Discover the skills and techniques required in an entry-level network administration interview and job Access the Sybex online learning center, with chapter review questions, full-length practice exams, hundreds of electronic flashcards, and a glossary of key terms Perfect as a standalone resource for those seeking to succeed on the CompTIA Network+ N10-008 exam or as a companion to the CompTIA Network+ Study Guide and CompTIA Network+ Deluxe Study Guide, this book is an indispensable reference for anyone preparing for a career in network administration, network analysis, or systems engineering.